Improving the adsorption characteristics and antioxidant activity of oat bran by superfine grinding. Issue 1 (15th September 2022) - Zhang, Yakun; Zhang, Meili; Guo, Xinyue; Bai, Xue; Zhang, Jing; Huo, Rui; Zhang, YuanYuan
Abstract: Oat bran (OB) is a by‐product of oat, which is rich in β‐glucan. As a new food processing technology, ultrafine powder can improve the surface properties of samples. OB with different grinding times was prepared, and its functional components, physical properties, adsorption properties, and antioxidant properties were evaluated. Results showed that with increased grinding times, the average particle size of OB decreased significantly ( p  < .05). And the water‐holding capacity, swelling capacity, and water solubility index of OB increased significantly ( p  < .05), whereas the animal and vegetable oil‐holding capacities decreased. Oat bran could adsorb cholic acid and glucose, which was related to the time of superfine grinding. In addition, the antioxidant capacity of OB was improved after superfine grinding. Related analysis shows that there was significant positive relationship between β‐glucan, polyphenols and soluble dietary fibers and antioxidant indicators ( p  < .05). The Fourier transform infrared (FTIR) results showed that the FTIR spectra of OB powder with different crushing times were similar. On the basis of the above analyses, it is suggested that OB prepared by superfine grinding for 5 min had good physical and chemical properties and antioxidant properties and is widely used in food. Abstract : Ultrafine grinding can improve the antioxidant activity of oat bran (OB). The adsorption capacity of OB can be ameliorated after superfine grinding.